Socio-economic and Psychological Impact of COVID-19 on English Learners - Jha, Ranjana Kumari (Journal of NELTA Gandaki, 2020)
The COVID-19 crisis has brought up unprecedented and complex issues for us all. COVID-19 crisis has made global impact in most of the sectors, including socio-economic and psychological impacts. Therefore, this study designed to address socio-economic and psychological impacts of COVID-19 on English learners. For this purpose, a sample of 50 students and 4 teachers were selected from two schools following random sampling procedures. Similarly, two key tools for collecting data were used, namely questionnaires and interviews. After analyzing the data collected through the online questionnaire and interview sheet, it has been found that COVID-19 has affected on socio-economic and psychological factors. Most of the students do not always take online class because of lack of money. During COVID-19, students sell fruits on the way. Psychologically, students are weak. So, they try to commit suicide and students do not enjoy online classes because of the lack of creativity in online. Furthermore, almost all the teachers opined that the presences of students are very low in online classes because of poor economic condition. Thus, COVID-19 directly impacts English learners' all aspects of life.